How do different components of Effortful Control contribute to children’s mathematics achievement? - Sánchez-Pérez, Noelia; Fuentes, Luis J.; López-López, Jose Antonio; Pina, Violeta; González-Salinas, Carmen (Frontiers in Psychology, 2015)
This work sought to investigate the specific contribution of two different components of Effortful Control -attentional focusing and inhibitory control- to children’s mathematics achievement. The sample was composed of 142 children aged 9 to 12 years old. Effortful Control components were measured through the Temperament in Middle Childhood Questionnaire (TMCQ; parent´s report); math achievement was measured via teacher’s report and through the standard Woodcock-Johnson test. Additionally, the contribution of other cognitive and socio-emotional processes was taken into account. Our results showed that only attentional focusing significantly contributed to the variance of children’s mathematics achievement; interestingly, mediational models showed that the relationship between effortful attentional self-regulation and mathematics achievement was mediated by academic peer popularity, as well as by intelligence and study skills. Results are discussed in the light of the current theories on the role of children’ self-regulation abilities in the context of school.